Total laparoscopic hysterectomy versus total abdominal hysterectomy with bilateral salpingo-oophorectomy for endometrial carcinoma: a randomised controlled trial with 5-year follow-up - Kluivers, Kirsten B. (Springer-Verlag, 2011)
This report is on recovery and long-term outcomes in a small-scale randomised controlled trial (RCT) after total laparoscopic hysterectomy versus total abdominal hysterectomy in (potential) endometrial carcinoma patients. An RCT was performed among women with atypical endometrial hyperplasia and endometrial carcinoma scheduled for hysterectomy in a teaching hospital in The Netherlands. Women were randomised to total laparoscopic hysterectomy versus total abdominal hysterectomy both with bilateral salpingo-oophorectomy and were followed until 5 years after the intervention. Patients completed the RAND 36-Item Short Form Health Survey (RAND-36), Quality of Recovery-40 (QoR-40) and Recovery Index-10 (RI-10) until 12 weeks after surgery. Main outcome measure was quality of life and recovery in the first 12 weeks after surgery. A linear mixed model was used for statistical analysis while accounting for baseline values where applicable. Seventeen women were included, of whom 11 allocated to the laparoscopic arm and 6 to the abdominal arm. Laparoscopic hysterectomy performed better on all scales and subscales used in the study. A statistically significant treatment effect, favouring laparoscopic hysterectomy, was found in the total RAND-36 (difference between groups 142 units, 95% confidence interval 46; 236). Clinical follow-up was completed after median 60 months, but this study was too small for conclusions regarding the safety and survival. Laparoscopic hysterectomy results in better postoperative quality of life in the first 12 weeks after surgery when compared with abdominal hysterectomy.